Profiles of the mannequin : the cultural and historic impact of the mannequin - Feigenbaum, Eric (London : Bloomsbury Visual Arts, 2024)
"Profiles of the Mannequin tracks the history and evolution from the headless models of 1900 right up to today's moving and virtual mannequins as well as shifts in representation in gender, race and body type. Beautifully illustrated and engagingly told, there are also in-depth interviews with creative professionals recounting their experiences, philosophies and stories of the mannequin and its impact on our culture both as a utilitarian object, and as an artistic statement"--
Includes bibliographical references and index.
Keywords: Mannequins (Figures) -- History